IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP PEMBERANTASAN MINUMAN KERAS (DALAM PENEGAKAN PERDA NOMOR 21 TAHUN 2012) - Nur Fitrah; Masni Masni; Yusuf Daud (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2022)
The purpose of this research is to find out the extent of the implementation of local government policies in the eradication of liquor (In Enforcement of Regional Regulation Number 21 of 2012). In the process of this research, the researcher uses a type of qualitative research. By collecting data using observation and interviews. In the eradication of alcoholism, strict supervision from the government is needed. Liquor is a drink that contains a high alcohol content causing the consumer to lose consciousness, in Lombong Village there are still many distributions of liquor that do not have a distribution permit, thereby increasing the number of liquor users and making room for liquor consumption. The policy carried out by the Lombong Village government in eradicating liquor based on Regional Regulation Number 21 of 2012, concerning the procurement, distribution, sale, supervision, and control of liquor, was unable to reduce the number of distribution and abuse of liquor in the Lombong village community, because it was influenced by no the existence of strict sanctions from the local government, the habits of the Lombong village community and low education.